IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB KEENGGANAN MASYARAKAT BERURUSAN DENGAN PAJAK (STUDI EKSPLORASI MASYARAKAT DI KOTA PALEMBANG) - Setiawan, Antonius Singgih (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2014)
This study aims to identify people reluctance factors in dealing with taxes. Using a sample of 850 respondents and analyzed using descriptive statistical methods can be gathered that the peoples of the city of Palembang has a tendency reluctant in dealing with taxes, many factors identified to be the cause (1) The level of corruption of government officials/taxes are still high (2) Facilities provided by the government are not satisfactory (3) Lack of transparency in tax matters (4) Feeling not benefit from the tax (5) Tax rules are complex and changing, and (6) They do not understand the rules of taxation in Indonesia.Â